Occurrence State and Time-Shift Characteristics of Residual Oil in Low-Permeability Reservoirs After Long-Term Waterflooding in Changqing Oilfield - Yangnan Shangguan; Boying Li; Chunning Gao; Junhong Jia; Yongqiang Zhang; Jinghua Wang; Tao Xu (Energies)
This study focuses on a low-permeability sandstone reservoir in the Changqing Oilfield, aiming to elucidate the formation mechanism and occurrence state of residual oil during late-stage waterflooding development, thereby providing theoretical guidance for refined residual oil recovery. By integrating scanning electron microscopy (SEM), nuclear magnetic resonance (NMR), and digital core analysis, the oil–water occurrence state and dynamic characteristics during waterflooding were systematically investigated. NMR was employed to determine fluid distribution within core pores, while CT scanning was utilized to construct a 3D digital core model, enabling the identification of microscopic residual oil displacement and occurrence states at different flooding stages. The oil displacement efficiency was further analyzed based on variations in oil–water distribution and occurrence states within the core. The results demonstrate that pore and throat size and connectivity are the primary factors governing reservoir permeability. After high-pore-volume (PV) waterflooding, microscopic residual oil predominantly exists as dispersed droplets, films, and small-scale clusters or columns. Although prolonged high-PV waterflooding effectively expands the sweep volume, localized displacement efficiency declines, and reservoir heterogeneity adversely affects sweep volume maintenance. The post-flooding residual oil characteristics are collectively determined by the core’s local connectivity, wettability, and pore–throat morphology. This research systematically analyzes the occurrence patterns and evolutionary trends of residual oil in low-permeability reservoirs during long-term waterflooding, providing critical theoretical insights and technical support for enhanced oil recovery and residual oil exploitation.